Peningkatan Prestasi Belajar Siswa pada Materi Satuan Debit melalui Team Accelerated Instruction - Supriyati Supriyati (Paedagogie, 2019)
The prior study aimed at enhancing students’ achievement on competency in solving problems related to discharge units. It was conducted in Class IV SDN Cacaban 6 of Magelang in the first semester of the academic year of 2016/2017. A Team Accelerated Instruction was applied to learning as an action. Primary data related to students’ achievement were obtained through tests, while secondary data related to the learning process were obtained through documentary study and observation to support the discussion. The results revealed that there was an increase in students' understanding of the pre-cycle, Cycles I and Cycle II. The average score increased from 53.1, to 86 in Cycle I, and to 87 in Cycle II. Thus, the application of the Accelerated Instruction Team could enhance students’achievement in the discharge unit material.